Climate change affects the number of hours in the thermal ranges of chilli in North-Central Mexico - Medina García, Guillermo; Mena-Covarrubias, Jaime; Ruiz-Corral, José Ariel; Rodríguez-Moreno, Víctor Manuel; Soria-Ruiz, Jesús (Revista Mexicana de Ciencias Agrícolas, 2017)
In Mexico, chili cultivation has a long cultural tradition and is one of the main centers of origin and domestication. An average of 97,306 ha is planted annually in the north of the country. However, the productivity of the chili crop is very erratic due to biotic and abiotic factors that occur during its development. Extreme temperatures and water availability are two of the dominant abiotic stressors. The objective of this work was to know the effect of global warming, on the thermal range of the chili crop. A historical analysis was performed on the variation of the number of hours with temperature inside and outside the thermal range of chili, and a similar analysis in the climatic scenarios 2050 and 2070 in the RCPs 4.5 and 8.5. Both in the historical analysis and in the climatologies we found positive and negative effects of global warming. Global warming will favor chilli cultivation with a surface increase (22.6%) with hourly temperature within development thresholds (15 to 32 °C) and a surface increase (15.8%) within the optimum temperature range (18 to 28 °C). Chili cultivation will be limited by the increase (20.8%) in the surface area with hourly temperature above the upper threshold (32 °C) and an increase (18.5%) in the area with a night time temperature above the upper threshold of night temperature (18 °C) in RCP 4.5 and in climatology 2050. High temperature stress will have an eff ect on the yield decrease due to the negative eff ect on pollination and fruit binding processes.
Keywords: Capsicum annuum , global warming, hourly temperature, Mexico, RCP.